St. Louis Encephalitis Virus in the Southwestern United States: A Phylogeographic Case for a Multi-Variant Introduction Event - Ridenour, Chase L.; Cocking, Jill; Poidmore, Samuel; Erickson, Daryn; Brock, Breezy; Valentine, Michael; Roe, Chandler C.; Young, Steven J.; Henke, Jennifer A.; Hung, Kim Y.; Wittie, Jeremy; Stefanakos, Elene; et al. (Frontiers in Genetics, 2021)
Since the reemergence of St. Louis Encephalitis Virus (SLEV) in the Southwest United States, identified during the 2015 outbreak in Arizona, SLEV has been seasonally detected within Culex spp. populations of Maricopa and Yuma counties in Arizona; Riverside County, California; and Clark County, Nevada. Previous work revealed the 2015 outbreak was caused by an importation of SLEV genotype III, previously detected only in Argentina. However, little is known about when the importation occurred or the population dynamics since its arrival into the Southwest. In this study, we sought to determine whether the annual detection of SLEV in the Southwest is due to enzootic cycling or new importations. To address this question, we analyzed 174 SLEV genomes (142 sequenced as part of this study) using Bayesian phylogenetic analyses to estimate the date of arrival into the American Southwest and characterize the underlying population structure of SLEV. Phylogenetic clustering showed that SLEV variants circulating in Maricopa and Riverside counties form two distinct populations with little evidence of inter-county transmission to date. Alternatively, in 2019, Yuma and Clark counties experienced annual importations of SLEV that originated in Riverside and Maricopa counties. Finally, the earliest representatives of SLEV genotype III in the Southwest form a polytomy that includes both California and Arizona samples. We propose that the initial outbreak most likely resulted from the importation of a population of SLEV genotype III variants, perhaps in one or more bird flocks migrating north in 2013, rather than a single variant introduced by one bird